13C mannitol as a novel biomarker for measurement of intestinal permeability. Issue 7 (23rd February 2016) - Grover, M.; Camilleri, M.; Hines, J.; Burton, D.; Ryks, M.; Wadhwa, A.; Sundt, W.; Dyer, R.; Singh, R. J.
Abstract: Background: Gastrointestinal (GI) and non‐GI disorders are associated with altered intestinal permeability, which can be measured in vivo by urinary excretion after oral lactulose and mannitol ingestion. Inadvertent dietary consumption of 12 Carbon ( 12 C, regular) mannitol in food or from other sources may interfere with the test's interpretation. 13 Carbon ( 13 C) constitutes 1% of carbon in nature and 13 C mannitol is a stable isotope. Our aim was to determine the performance of 13 C mannitol for measurement of intestinal permeability. Methods: Ten healthy volunteers underwent intestinal permeability assay using coadministered 12 C mannitol, 13 C mannitol and lactulose, followed by timed urine collections. Urinary sugar concentrations were measured using tandem high performance liquid chromatography–mass spectrometry. Key results: We found that 13 C mannitol can be distinguishable from 12 C mannitol on tandem mass spectrometry. In addition, 13 C mannitol had 20‐fold lower baseline contamination compared to 12 C mannitol. We describe here the 13 C mannitol assay method for the measurement of intestinal permeability. Conclusions & Inferences: In conclusion, 13 C mannitol is superior to 12 C mannitol for measurement of intestinal permeability. It avoids issues with baseline contamination and erratic excretions during the testing period.